Detection of Clostridium difficile in Retail Ground Meat Products in Manitoba - Monique Visser; Shadi Sepehrim; Nancy Olson; Tim Du; Michael R Mulvey; Michelle J Alfa (Canadian Journal of Infectious Diseases and Medical Microbiology)
The aim of the present study was to determine whether Clostridium difficile was present in uncooked retail ground beef and ground pork products sold in Winnipeg, Manitoba. Using an alcohol treatment protocol and inoculation of cultures on C difficile Moxalactam Norfloxacin (CDMN), toxigenic C difficile was found in 6.3% of 48 meat samples. The C difficile isolates belonged to different pulsotypes, all of which had been previously isolated from the stool of Manitoba patients with C difficile disease. Because cooking of meat will not eradicate C difficile spores, this raises a concern regarding potential foodborne transmissibility of this organism.